SURVEI SIFAT FISIK DAN KANDUNGAN NUTRIEN ONGGOK TERHADAP METODE PENGERINGAN YANG BERBEDA DI DUA KABUPATEN PROVINSI LAMPUNG - I Nyoman Ari; Syahrio Tantalo; Liman . (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
Cassava into industrial waste which is generated in the form of wet tapioca . Utilization of cassava asanimal feed , usually first dried . The drying process can be done on the cement floor and on theground . The differences in the drying potential to provide different quality of nutrients .This study aimed to compare the nutritional composition and physical properties of the drying cassavaon the ground and the cement floor , and to know the method of drying on the ground or on a cementfloor the better the nutritional composition and physical properties of the onggok.Pelaksanaanresearch conducted at the Laboratory of Nutrition and Animal Feed Animal Husbandry Department ofthe Faculty of Agriculture, University of Lampung . This study uses data obtained will be analyzedusing Student's t-test at the 5% significance level.The results showed that : ( 1 ) there is a significant difference ( P > 0.05 ) in ash content, BETN levels; ( 2 ) there is no significant difference ( P < 0.05 ) in moisture content, protein content, fat content,and crude fiber.